2005
DOI: 10.1016/j.jmaa.2005.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Infinite propagation speed for the Degasperis–Procesi equation

Abstract: We prove that any nontrivial classical solution of the Degasperis-Procesi equation will not have compact support if its initial data has this property.  2005 Elsevier Inc. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
50
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(50 citation statements)
references
References 21 publications
0
50
0
Order By: Relevance
“…Matsuno [36] studied multisoliton solutions and their peakon limits. Analogous to the case of Camassa-Holm equation [8], Henry [25] showed that smooth solutions to Eq. (1.2) have infinite speed of propagation.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Matsuno [36] studied multisoliton solutions and their peakon limits. Analogous to the case of Camassa-Holm equation [8], Henry [25] showed that smooth solutions to Eq. (1.2) have infinite speed of propagation.…”
mentioning
confidence: 94%
“…[5,25,30,31,32,36,44,45,46,47] and the citations therein. For example, Yin proved local well-posedness of Eq.…”
mentioning
confidence: 99%
“…Important contributions to the study of the DP equation were also made by Matsuno and Henry et al (see e.g. [13,31]). …”
Section: Introductionmentioning
confidence: 99%
“…Matsuno [48] studied multisoliton solutions and their peakon limits. Analogous to the case of the Camassa-Holm equation [11,35], Henry [34] showed that smooth solutions to the Degasperis-Procesi equation have infinite speed of propagation (see also [49]). Coclite and Karlsen [9] also obtained global existence results for entropy weak solutions in the class of L 1 (R) ∩ BV (R) and the class of…”
mentioning
confidence: 98%
“…Since the Degasperis-Procesi equation was derived, many papers were devoted to its study; cf. [9,31,34,42,44,45,46,47,48,55] and the citations therein. For example, Yin proved local well-posedness to (1.5) with initial data u 0 ∈ H s , s > 3 2 on the line [55] and the precise blow-up scenario and a blow-up result were derived.…”
mentioning
confidence: 99%